1999
DOI: 10.1063/1.480275
|View full text |Cite
|
Sign up to set email alerts
|

Surface diffusion potential energy surfaces from first principles: CO chemisorbed on Pt{110}

Abstract: Lateral potential energy curves for the chemisorption of CO on Pt{110} (1×1) and (1×2) along different azimuthal directions have been calculated using density functional theory slab calculations. In contrast to the simple models almost universally used, the results along 〈11̄0〉 show that there is a barrier of ∼0.15 eV between bridge and atop sites. Both bridge and atop sites are local minima. Diffusion along 〈100〉 on the (1×1) surface is strongly inhibited by a barrier ⩾1.2 eV. Quasielastic helium atom scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…Lewis and Rappe [20] report for the same site (top) a lower adsorption energy, but still too high (in absolute value) compared to experiment (E ads = −1.239 eV). Although Ge and King [21,22] found that bonding at the bridge site is stronger by 80 meV than in the top site, and a barrier between the top and the bridge site which was not observed in a helium atom scattering experiment (HAS) [23,24]. Finally, we know of only one attempt to study CO on the Cu(001) surface including the generalized gradient approximation (GGA) for the exchange-correlation functional [25].…”
Section: Introductionmentioning
confidence: 99%
“…Lewis and Rappe [20] report for the same site (top) a lower adsorption energy, but still too high (in absolute value) compared to experiment (E ads = −1.239 eV). Although Ge and King [21,22] found that bonding at the bridge site is stronger by 80 meV than in the top site, and a barrier between the top and the bridge site which was not observed in a helium atom scattering experiment (HAS) [23,24]. Finally, we know of only one attempt to study CO on the Cu(001) surface including the generalized gradient approximation (GGA) for the exchange-correlation functional [25].…”
Section: Introductionmentioning
confidence: 99%
“…5,11 In particular, for CO/Pt͑111͒ the curvature of the potential provided by the T-mode frequencies in the bridge and on-top sites, coupled with the potential energy difference available via the temperature dependence of the occupation probabilities, 17 indicate a diffusion barrier of 130 meV, 13 the same as the value measured with QHAS 13 and calculated by Ge and King for CO/Pt͑110͒. 1 It is clear that their comparison of CO/Pt͑110͒ with CO/Cu͑001͒ is not appropriate since, unlike CO/Pt͑111͒, for which two adsorption sites clearly exist and contribute to the shape of the PES, CO is observed to occupy exclusively on-top sites on Cu͑001͒, even under compression. 18 In summary, the length scale information provided by QHAS rules out intrasite diffusional motion as an explanation of the measured QHAS broadening.…”
mentioning
confidence: 82%
“…͑1͒ In their article Ge and King claim that very short, intrasite jumps are responsible for the quasielastic broadening observed in previous QHAS studies. 1 Motions within the unit cell ͑length scales less than lϷ1 Å͒ correspond to parallel momentum transfers of ⌬KϾ6 Å Ϫ1 and, consequently, do not contribute to the quasielastic broadening in the ⌬K ranges reported for the QHAS measurements (0Ͻ⌬Kр3 Å Ϫ1 , lϷ2 -ϱ Å͒. Further, in the small momentum transfer limit, corresponding to long length scales (lϭ2/⌬K) much greater than one lattice constant, the microscopic details of the diffusional motion are averaged out over many jumps.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations